Fabrication of silver nanoisland films by pulsed laser deposition for surface-enhanced Raman spectroscopy - Budner, Bogusław; Kuźma, Mariusz; Nasiłowska, Barbara; Bartosewicz, Bartosz; Liszewska, Malwina; Jankiewicz, Bartłomiej J. (Beilstein Journal of Nanotechnology, 2019)
The results of studies on the fabrication and characterization of silver nanoisland films (SNIFs) using pulsed laser deposition (PLD) and the evaluation of these films as potential surface-enhanced Raman scattering (SERS) substrates are reported. The SNIFs with thicknesses in a range of 4.7 ± 0.2 nm to 143.2 ± 0.2 nm were deposited under different conditions on silicon substrates. Size and morphology of the fabricated silver nanoislands mainly depend on the substrate temperature, and number and energy of the laser pulses. SERS properties of the fabricated films were evaluated by measuring SERS spectra of para-mercaptoaniline (pMA) molecules adsorbed on them. SERS enhancement factors are shown to depend on the SNIF morphology, which is modified by changes of the deposition conditions. The highest enhancement factor in the range of 105 was achieved for SNIFs that have oval and circular silver nanoislands with small distances between them.
Keywords: nanofabrication; pulsed laser deposition; SERS substrates; silver nanoisland films; surface-enhanced Raman spectroscopy; X-ray photoelectron spectroscopy

(untitled) - Cialla-May, D.; Zheng, X.-S.; Weber, K.; Popp, J. (Chem. Soc. Rev., 2017)

(untitled) - Yu, B.; Ge, M.; Li, P.; Xie, Q.; Yang, L. (Talanta, 2019)

(untitled) - Laing, S.; Jamieson, L. E.; Faulds, K.; Graham, D. (Nat. Rev. Chem., 2017)

(untitled) - Bartosewicz, B.; Andersson, P. O.; Dzięcielewski, I.; Jankiewicz, B.; Weyher, J. L. (Mater. Sci. Semicond. Process., 2019)

(untitled) - Liszewska, M.; Bartosewicz, B.; Budner, B.; Nasiłowska, B.; Szala, M.; Weyher, J. L.; Dzięcielewski, I.; Mierczyk, Z.; Jankiewicz, B. J. (Vib. Spectrosc., 2019)

(untitled) - Cialla, D.; März, A.; Böhme, R.; Theil, F.; Weber, K.; Schmitt, M.; Popp, J. (Anal. Bioanal. Chem., 2012)

(untitled) - Wang, P.; Huang, B.; Dai, Y.; Whangbo, M. H. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Valenti, M.; Jonsson, M. P.; Biskos, G.; Schmidt-Ott, A.; Smith, W. A. (J. Mater. Chem. A, 2016)

(untitled) - Bricchi, B. R.; Ghidelli, M.; Mascaretti, L.; Zapelli, A.; Russo, V.; Casari, C. S.; Terraneo, G.; Alessandri, I.; Ducati, C.; Li Bassi, A. (Mater. Des., 2018)

(untitled) - Clavero, C. (Nat. Photonics, 2014)

(untitled) - Rodrigues, M. S.; Costa, D.; Domingues, R. P.; Apreutesei, M.; Pedrosa, P.; Martin, N.; Correlo, V. M.; Reis, R. L.; Alves, E.; Barradas, N. P.; Sampaio, P.; Borges, J.; et al. (Appl. Surf. Sci., 2018)

(untitled) - Ko, H.; Singamaneni, S.; Tsukruk, V. V. (Small, 2008)

(untitled) - Dhand, C.; Dwivedi, N.; Loh, X. J.; Jie Ying, A. N.; Verma, N. K.; Beuerman, R. W.; Lakshminarayanan, R.; Ramakrishna, S. (RSC Adv., 2015)

(untitled) - Cañamares, M. V.; Garcia-Ramos, J. V.; Sanchez-Cortes, S.; Castillejo, M.; Oujja, M. (J. Colloid Interface Sci., 2008)

(untitled) - Besner, S.; Kabashin, A. V.; Winnik, F. M.; Meunier, M. (Appl. Phys. A: Mater. Sci. Process., 2008)

(untitled) - Drachev, V. P.; Thoreson, M. D.; Nashine, V.; Khaliullin, E. N.; Ben-Amotz, D.; Davisson, V. J.; Shalaev, V. M. (J. Raman Spectrosc., 2005)

(untitled) - Gracia-Pinilla, M. Á.; Pérez-Tijerina, E.; Antúnez-García, J.; Fernández-Navarro, C.; Tlahuice-Flores, A.; Mejía-Rosales, S.; Montejano-Carrizales, J. M.; José-Yacamán, M. (J. Phys. Chem. C, 2008)

(untitled) - Mandal, S. K.; Roy, R. K.; Pal, A. K. (J. Phys. D: Appl. Phys., 2002)

(untitled) - Ghidelli, M.; Mascaretti, L.; Bricchi, B. R.; Zapelli, A.; Russo, V.; Casari, C. S.; Li Bassi, A. (Appl. Surf. Sci., 2018)

(untitled) - Kamakshi, K.; Silva, J. P. B.; Sekhar, K. C.; Marslin, G.; Moreira, J. A.; Conde, O.; Almeida, A.; Pereira, M.; Gomes, M. J. M. (Appl. Phys. B: Lasers Opt., 2016)

(untitled) - D’Andrea, C.; Neri, F.; Ossi, P. M.; Santo, N.; Trusso, S. (Laser Phys., 2011)

(untitled) - Verma, S.; Rao, B. T.; Bhartiya, S.; Sathe, V.; Kukreja, L. M. (Appl. Surf. Sci., 2015)

(untitled) - Fazio, E.; Neri, F.; D'Andrea, C.; Ossi, P. M.; Santo, N.; Trusso, S. (J. Raman Spectrosc., 2011)

(untitled) - Agarwal, N. R.; Neri, F.; Trusso, S.; Lucotti, A.; Ossi, P. M. (Appl. Surf. Sci., 2012)

(untitled) - Smyth, C. A.; Mirza, I.; Lunney, J. G.; McCabe, E. M. (Appl. Surf. Sci., 2013)

(untitled) - Koch, R.; Hu, D.; Das, A. K. (Phys. Rev. Lett., 2005)

(untitled) - Maitani, M. M.; Ohlberg, D. A. A.; Li, Z.; Allara, D. L.; Stewart, D. R.; Williams, R. S. (J. Am. Chem. Soc., 2009)

(untitled) - Taylor, C. E.; Pemberton, J. E.; Goodman, G. G.; Schoenfisch, M. H. (Appl. Spectrosc., 1999)

(untitled) - Kudelski, A. (Vib. Spectrosc., 2005)

(untitled) - Wu, D.-Y.; Liu, X.-M.; Duan, S.; Xu, X.; Ren, B.; Lin, S.-H.; Tian, Z.-Q. (J. Phys. Chem. C, 2008)

(untitled) - Campion, A.; Ivanecky, J. E.; Child, C. M.; Foster, M. (J. Am. Chem. Soc., 1995)

(untitled) - Weyher, J. L.; Bartosewicz, B.; Dzięcielewski, I.; Krajczewski, J.; Jankiewicz, B.; Nowak, G.; Kudelski, A. (Appl. Surf. Sci., 2019)

(untitled) - Zheng, J.; Zhou, Y.; Li, X.; Ji, Y.; Lu, T.; Gu, R. (Langmuir, 2003)

(untitled) - Álvarez-Puebla, R. A. (J. Phys. Chem. Lett., 2012)

(untitled) - Ye, J.; Hutchison, J. A.; Uji-i, H.; Hofkens, J.; Lagae, L.; Maes, G.; Borghs, G.; Van Dorpe, P. (Nanoscale, 2012)

(untitled) - Osawa, M.; Matsuda, N.; Yoshii, K.; Uchida, I. (J. Phys. Chem., 1994)

(untitled) - Adrian, F. J. (J. Chem. Phys., 1982)

(untitled) - Huang, Y.-F.; Zhu, H.-P.; Liu, G.-K.; Wu, D.-Y.; Ren, B.; Tian, Z.-Q. (J. Am. Chem. Soc., 2010)

(untitled) - Dong, B.; Fang, Y.; Xia, L.; Xu, H.; Sun, M. (J. Raman Spectrosc., 2011)